Effects of 17β-Estradiol on Monocyte/Macrophage Response to Staphylococcus aureus: An In Vitro Study - Souza, Clarissa Leal Silva e; Barbosa, Camila Dutra; Coelho, Hanna I. L. N.; Santos Júnior, Manoel N.; Barbosa, Elaine Novaes; Queiroz, Éllunny Chaves; Teles, Mauro Fernandes; dos Santos, Déborah Cruz; Bittencourt, Rafaela Souza; Soares, Telma de Jesus; Oliveira, Márcio Vasconcelos; Timenetsky, Jorge; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
To describe how 17β-estradiol (E2) influence in the monocyte/macrophage response induced by S. aureus in in vitro models of murine peritoneal macrophages (MPMs) and human peripheral blood monocytes (HPBM). MPMs (2 x 105/ml) were isolated from sham (n=3) and ovariectomized (OVX) females (n = 3) and males (n = 3) after induction by thioglycolate. The MPMs obtained from OVX females and males were treated for 24 hours with 17β-estradiol (E2) (10-7 M), and after that, inoculation with S. aureus was carried out for 6 hours. The macrophages were collected and destined to evaluate the relative gene expression of TNF-α, IL-1β, IL-6, IL-8 and TLR2. For the in vitro model of HPBMs, six men and six women of childbearing age were selected and HPBMs were isolated from samples of the volunteers' peripheral blood. In women, blood was collected both during menstruation and in the periovulatory period. HPBMs were inoculated with S. aureus for 6 hours and the supernatant was collected for analysis of cytokines by Luminex and the HPBMs were removed for analysis of 84 genes involved in the host's response to bacterial infections by RT-PCR array. Previous treatment with E2 decreased the gene expression and production of proinflammatory cytokines, such as TNF-α, IL-1β and IL-6 and decreased the expression of TLR2 tanto em MPMs quanto em HPBMs. The analysis of gene expression shows that E2 inhibited the NFκB pathway. It is suggested that 17β-estradiol acts as an immunoprotective in the monocyte/macrophage response induced by S. aureus.